(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the types and proper use of lacunas in English language. Article begins by defining linguacultural analysis and its key elements including the examples of the languages in various contexts in which they were used.